2012
DOI: 10.4141/cjss2011-070
|View full text |Cite
|
Sign up to set email alerts
|

Long-term grazing effects on grassland soil properties in southern British Columbia

Abstract: Evans, C. R. W., Krzic, M., Broersma, K. and Thompson, D. J. 2012. Long-term grazing effects on grassland soil properties in southern British Columbia. Can. J. Soil Sci. 92: 685–693. Although grazing effects on soil properties have been evaluated on various temperate grasslands, no study has dealt with these effects in the southern interior of British Columbia. The objective of this study was to determine the effects of spring versus fall season grazing as well as grazing [at a moderate rate of 0.6 ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 31 publications
5
41
1
1
Order By: Relevance
“…Reduced root allocation usually influences soil C inputs and also decreases N retention within the soil (Derner et al 2006). Our results confirm the findings of Evans et al (2012) who reported reduced SOC when lands grazed during plant growing season (spring to summer) partly due to increased soil compaction. On the other hand, in the WG treatment vegetation was usually grazed after fully matured, and as a result plants were resistant to grazing pressure (Du Toit et al 2011).…”
Section: Water Infiltration Rate and Volumetric Water Contentsupporting
confidence: 90%
See 2 more Smart Citations
“…Reduced root allocation usually influences soil C inputs and also decreases N retention within the soil (Derner et al 2006). Our results confirm the findings of Evans et al (2012) who reported reduced SOC when lands grazed during plant growing season (spring to summer) partly due to increased soil compaction. On the other hand, in the WG treatment vegetation was usually grazed after fully matured, and as a result plants were resistant to grazing pressure (Du Toit et al 2011).…”
Section: Water Infiltration Rate and Volumetric Water Contentsupporting
confidence: 90%
“…reported for arid rangelands (Lal 2000). The C and N stock obtained in this study is closer to the average for Africa (Beukes and Cowling 2003;Koetze et al 2013) while smaller than reports elsewhere in the world (Evans et al 2012;Liu et al 2012). ).…”
Section: Water Infiltration Rate and Volumetric Water Contentsupporting
confidence: 64%
See 1 more Smart Citation
“…The high concentration of resting sites in the Dis and Poa communities may cause significant soil compaction to a greater extent than reported for cattle use in the Pse community (Evans et al 2012) because the risk of soil compaction is greater for wet soil. Soil compaction in the Dis community may reduce habitat quality for the Great Basin spadefoot toad, a species at risk, which inhabits these ephemeral ponds (Karl Larsen, unpublished observation).…”
Section: Resting Electivitymentioning
confidence: 91%
“…Trampling of grazing animals was reported to affect soil by increasing bulk density and mechanical resistance, and reducing porosity, water infiltration, and aggregate stability (Evans et al, 2012). Zhou et al (2010) denoted that grazing and trampling by livestock cause deterioration of soil physical properties and increased soil erodibility.…”
Section: Discussionmentioning
confidence: 99%